Globalization And Digitization In A Developing Economy: Opportunities, Challenges And Ways Forward (Zien Journal of Social Sciences and Humanities, 2025)
This study examines the influence of Uzbek national traditions on the ethical and aesthetic progress of society. By analyzing cultural practices such as communal cooperation (hashar), hospitality (mehmondo’stlik), and traditional arts, the research highlights their role in shaping moral values, social cohesion, and aesthetic sensibilities. Qualitative methods, including interviews and case studies, reveal that these traditions foster collective responsibility, respect for heritage, and artistic expression. However, globalization and urbanization pose challenges to their preservation. The findings emphasize the need to integrate traditional values into modern frameworks to sustain societal development. This work contributes to understanding cultural mechanisms in ethical-aesthetic education and offers insights for policymakers